Optic Disc Features in Familial Retinal Arteriolar Tortuosity - Sinner, Veronika; Heckmann, Jan; Sturm, Veit; Valmaggia, Christophe; Todorova, Margarita G (Klinische Monatsblatter fur Augenheilkunde, 2021)
Describing optic disc appearance in familial retinal arteriolar tortuosity (fRAT) using multimodal imaging and raising awareness of peripapillary arterial changes due to this disorder. A cross-sectional study was performed in four consecutive patients of two non-related families. Detailed ophthalmological examination was performed and supported by medical and family history and multimodal imaging. In all subjects, increased tortuosity of second- and third-order retinal arteries in superior and deeper vascular plexus was documented. Furthermore, tortuosity in the peripapillary circle of Zinn-Haller was found. In addition, retinal vessel oximetry confirmed tortuosity only of the arterial vessels. The present data suggests that a blurry bordered, hyperemic optic disc in the presence of abnormally tortuous arteriolar vessels and asymptomatically or oligosymptomatically spontaneously resolved hemorrhages could be associated with a fRAT. This finding could be linked to peripapillary arterial vessel tortuosity.